169k views
3 votes
(ii) 3x - 5y - 4 = 0 and 9x = 2y +7​

User Gdgr
by
5.1k points

2 Answers

5 votes

Explanation:

3×‐9×-5y-2y =0-7

-6x-7y =-7

User Arackna
by
5.4k points
4 votes

Answer:


x = (9)/(13) \ , \ y = - (5)/(13)

Explanation:

3x - 5y = 4 ----------- ( 1 )

9x - 2y = 7 -----------( 2 )

______________________

( 1 ) x 9 => 27x - 45y = 36 ----------------- ( 3 )

( 2) x 3 => 27x - 6y = 21 -------------------( 4 )

_____________________

( 3 ) => 27x - 45y = 36

- ( 4 ) => -27x + 6y = - 21

____________________

( 3 ) - ( 4 ) => 0x - 39y = 15

-39y = 15


y = (15)/(-39) = -(5)/(13)

Substitute y in ( 1 ) :


3x - 5y = 4\\\\3x - ( 5 * -(5)/(13)) = 4\\\\3x + (25)/(13) = 4\\\\3x = 4 - (25)/(13)\\\\3x = (52 - 25)/(13)\\\\3x = (27)/(13)\\\\x = (27)/(13 * 3)\\\\x= (9)/(13)

User Richard Pennington
by
5.4k points